Dry grasslands on fluvial terraces of the middle reaches of river Piave in the North East Italy context - Tasinazzo, Stefano; Zanatta, Katia; Lasen, Cesare; Fiorentin, Roberto (Hacquetia, 2021)
Dry grassland vegetation on fluvial terraces along middle reaches of river Piave and river Brenta in Northeastern high Po plain were investigated through a phytosociological approach. Comparisons with ecologically analogous communities described from neighbouring territories lead to the description of a new association belonging to Centaureion dichroanthae alliance: Astragalo onobrychidis-Koelerietum pyramidatae. Residual fragments of Chrysopogon gryllus-dominated grassland on slighly deeper soils are refered to Chamaecytiso hirsuti-Chrysopogonetum grylli.